Co-combustion behaviours of a low calorific Uruguayan Oil Shale with biomass wastes. (15th April 2020) - Torres, Martín; Portugau, Patrice; Castiglioni, Jorge; Cuña, Andrés; Yermán, Luis
Highlights: I-cone, TPS and TGA-FTIR were used to characterize OS-biomass blends. Combustion gas pollutants of the Uruguayan Oil Shale were quantified. Unpublished thermal properties of OS and biomasses are reported. The addition of biomass to the OS improves the combustion index. EG containing 50% of OS or less turned out be suitable for industrial processes. Abstract: In the present work thermal transport properties, thermochemical characteristics and gaseous pollutants released during co-combustion of different biomasses with oil shales (OS) were assessed using three different mass ratios (25%, 50% and 75% OS-biomass). The biomasses selected for carrying out the analysis were grape pomace (GP), rice husk (RH) and eucalyptus grandis (EG). In this sense, we demonstrated that the addition of biomass to the OS turns out having a positive effect, it improves the combustion index and diminishes the amount of pollutant emissions per energy unit released. Cone calorimeter tests were carried out in order to determine the effective heat of combustion (EHC) and subsequently the energetic combustion efficiency (EHC/HHV) taking as reference the higher heating value (HHV). The higher thermal diffusivity value was obtained for EG (0.161 mm 2 /s) and the lowest value was obtained for GP (0.105 mm 2 /s). The EHC/HHV ratio was obtained for a blending proportion of 50% for OS-EG (0.88–0.98). According to combustion index results, blends containing c.a 50% OS-EG reached a good burning performance of the combustion process, providing a potential OS-biomass ratio for being used as fuel. Moreover, the co-combustion emissions per energy unit released were analysed by means of TG-FTIR. CO2, CO and SO2 patterns showed that the emissions diminished with the addition of biomass to the OS. This paper aims to perform an assessment of the potential utilization of OS-biomass blends based on the biomass and OS composition, their thermal properties, gas emissions per energy unit released and EHC/HHV ratio.